2021
DOI: 10.7150/jca.57894
|View full text |Cite
|
Sign up to set email alerts
|

An Italian National Survey on Ovarian Cancer Treatment at first diagnosis. There's None so Deaf as those who will not Hear

Abstract: Objective: Epithelial ovarian cancer (EOC) is the most lethal gynecological malignancy, crucial prognostic factors are no gross residual disease and centralization of cases. To evaluate the centralization of EOC patients, we report the results of a survey that shows the daily management of EOC patients in Italy. Methods: A 49-items electronic unblinded survey assessing demographics, practice characteristics, current opinions and approach to managing advanced EOC at first diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The centralization of oncological treatment improves survival with a simultaneous reduction in complications [16]. In Italy, most surgeries for ovarian cancer were performed by general gynecologists, but their oncological results were worse than those of gynecologic oncologists [17]. Recently, similar observations were reported by Jochum et al during the International Gynecologic Cancer Society Congress in New York [18].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The centralization of oncological treatment improves survival with a simultaneous reduction in complications [16]. In Italy, most surgeries for ovarian cancer were performed by general gynecologists, but their oncological results were worse than those of gynecologic oncologists [17]. Recently, similar observations were reported by Jochum et al during the International Gynecologic Cancer Society Congress in New York [18].…”
Section: Discussionmentioning
confidence: 71%
“…They concluded that high-volume centers are expected to improve the prognosis of ovarian cancer; moreover, adequate management of comorbidities and postoperative complications are expected in high-volume centers. Although centralization of treatment can cause barriers related to long travel, improvements in oncological outcome fully justifies the development of high-volume centers [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the Emilia-Romagna regional audit reported that most of the hospitals that treated EOC patients were low-volume centers and only 45.6% of EOC patients were treated in high-volume centers, where they achieved significantly better survival. [11][12][13][14] A recent Italian national survey on EOC treatment showed that EOC patients are still treated by general gynecologists despite the well-known detrimental effect on survival. 13 Regional data from 2017-2018 showed a wide dispersion of surgeries for EOC patients, 22 hospitals surgically treated at least one case of EOC and 15 hospitals treated fewer than 10 EOC patients/year.…”
Section: (Figo [The International Federation Of Gynecology and Obstet...mentioning
confidence: 99%
“…[11][12][13][14] A recent Italian national survey on EOC treatment showed that EOC patients are still treated by general gynecologists despite the well-known detrimental effect on survival. 13 Regional data from 2017-2018 showed a wide dispersion of surgeries for EOC patients, 22 hospitals surgically treated at least one case of EOC and 15 hospitals treated fewer than 10 EOC patients/year. 14 To ensure adequate care and the best treatment for EOC patients and so guarantee the best prognosis, the Emilia-Romagna Region enacted a regional decree in December 2019 intended to centralize the care of ovarian cancer patients in which it proposed an oncology network based on the hub-and-spoke model.…”
Section: (Figo [The International Federation Of Gynecology and Obstet...mentioning
confidence: 99%
See 1 more Smart Citation